The synergistic effect of PDT and oxacillin on clinical isolates of Staphylococcus aureus - Iluz, Natanel; Maor, Yasmin; Keller, Natan; Malik, Zvi (Lasers in surgery and medicine, 2018)
Background Staphylococcus aureus is a major pathogen in clinical microbiology. It is known to cause infections at various body sites and can be life‐threatening. The development of resistance to many well‐established antibiotic treatments and the prevalence of methicillin‐resistant S. aureus (MRAS) among hospital patients and the general community pose challenges in treating the pathogen. The antimicrobial effect of photodynamic therapy (PDT) has been a subject of study for a long time and can offer new strategies for dealing with resistant strains. Objective In our study, we searched for a positive synergistic relationship between PDT and the standard antibiotics used to treat S. aureus and MRSA infections. Materials and Methods The phototoxic profile of deuteroporphyrin (DP) in both resistant and susceptible clinical strains of S. aureus was determined by plating of treated and untreated broth cultures. Electron microscopy imaging was done to explore possible sites of damage and free‐radical accumulation in the cells during DP‐PDT. Minimal inhibitory concentration (MIC) of oxacillin, gentamicin, vancomycin, rifampin, and fusidic acid was determined using the broth dilution method, and the checkerboard method was used to detect and evaluate the synergistic potential of DP‐PDT and antibiotic combinations. A synergistic combination was further characterized using broth cultures and plating. Results DP‐PDT using a light dose of 15 J/cm2 showed a bactericidal effect even with a small concentration of 17 μM DP. Transmission electron microscopy indicated profound damage in the cell wall and cell membrane, and the appearance of mesosome‐like structures. Free radicals tend to localize in the cell membrane and inside the mesosome. No synergistic effect was detected by combining PDT with gentamicin, vancomycin, rifampin, and fusidic acid treatments. A positive synergistic effect was observed only in DP‐PDT‐oxacillin combined treatment using the checkerboard method. The effect was observed in clinical antibiotic‐resistant isolates after DP‐PDT using a light dose of 46 J/cm2 and small concentrations of DP. Oxacillin MIC decreased below 2 μg/ml in resistant strains under such conditions. Cultures which did not undergo new cycles of DP‐PDT recovered their original oxacillin resistance after a few generations. Conclusions PDT with porphyrins shows possible new therapeutic options in treating drug‐resistant S. aureus at body sites suitable for irradiation. The synergistic effect of DP‐PDT with oxacillin on clinical strains illustrates the potential of PDT to augment traditional antibiotic treatment based on cell wall inhibitors. Lasers Surg. Med. 50:535–551, 2018. © 2018 Wiley Periodicals, Inc.